Designer Colloidal Layers of Disordered Plasmonic Nanoparticles for Light Extraction. (30th June 2016) - Jouanin, Anthony; Hugonin, Jean Paul; Lalanne, Philippe
Abstract : Basic design rules are disclosed for broadband light‐extraction colloidal films formed with disordered ensembles of plasmonic particles. They are derived through the numerical study of a test‐bed geometry consisting of a low‐refractive index slab in air. Albeit simple, the geometry encompasses many physically effects encountered in real light‐emitting devices, including the pronounced absorption at the peak of the nanoparticles resonance spectrum, the anisotropy of the radiation diagram of nanoparticles in waveguides and unavoidable coherent multiple interferences that ruin the predictive strength of first‐order scattering models. How we can simultaneously take advantage of (1) the shape or size of the individual nanoparticles, (2) their transverse position with respect to the guiding photonic structure, (3) their concentration, and (4) the structural topology of the disorder ensemble are illustrated. Following this approach, a threefold enhancement in the extraction efficiency can be reached as compared to a film without plasmonic particles. It is also predicted that the extraction rapidly saturates and then decreases as the nanoparticle density increases, suggesting that best performance is achieved at low concentrations. Spectrally broad and directionally random far‐field radiation diagrams are additionally reported, which do not suffer from deterministic interferential behaviors observed at particular wavelengths and directionalities with periodic light‐extraction structures. Abstract : With advanced electromagnetic‐computation tools, the optical properties of colloidal add‐layers composed of random arrays of hundreds of metallic nanoparticles are studied. General guidelines on how to engineer nanoparticle shape and disorder structural topology to maximize the extraction efficiency are proposed.